2022
DOI: 10.1038/s41598-022-12637-z
|View full text |Cite
|
Sign up to set email alerts
|

Group VR experiences can produce ego attenuation and connectedness comparable to psychedelics

Abstract: With a growing body of research highlighting the therapeutic potential of experiential phenomenology which diminishes egoic identity and increases one’s sense of connectedness, there is significant interest in how to elicit such ‘self-transcendent experiences’ (STEs) in laboratory contexts. Psychedelic drugs (YDs) have proven particularly effective in this respect, producing subjective phenomenology which reliably elicits intense STEs. With virtual reality (VR) emerging as a powerful tool for constructing new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…Glowacki et al created a VR framework called ‘Isness-distributed’ (Isness-D) based on the premise that VR could be a mechanism for devising a new perceptual milieu. 10 This study demonstrated that intersubjective STEs could be designed by using distributed VR, where individuals disperse their sense of self in connection to others.…”
Section: Metaverse and Healthcarementioning
confidence: 77%
“…Glowacki et al created a VR framework called ‘Isness-distributed’ (Isness-D) based on the premise that VR could be a mechanism for devising a new perceptual milieu. 10 This study demonstrated that intersubjective STEs could be designed by using distributed VR, where individuals disperse their sense of self in connection to others.…”
Section: Metaverse and Healthcarementioning
confidence: 77%
“…A more successful endeavor involves the recent work of Glowacki et al (2020, 2022) who developed the scripted, multiuser VR they titled “Isness.” In their first evaluation of Isness, Glowacki et al (2020) utilized colocated groups of up to four users in a single room who were visible to each other through HMD as depicted as avatars that shifted through various esthetic states, for example, by size, color, distribution, density, and latency of light parameters. Some of these alterations depended, in part, on user-generated actions, specifically, by their adopting a “mudra pose,” that is, bringing the tip of either thumb to either the tip of their same-handed forefinger or middle finger, behaviors that were tracked by custom-made VR compatible gloves.…”
Section: The Present Studymentioning
confidence: 99%
“…Cyberdelic media present themselves as an alternative to the deleterious effects of contemporary digital media: media that cultivate harmony, awe, and presence rather than FOMO and dispersion, produce effects similar to those of the mystical-type experiences elicited by psychedelics, and are aligned with the aim of spiritual growth (Arnott, 2018;Glowacki et al, 2022;Smith and Warner, 2022). The cyberdelic project bases itself on the appealing suggestion that rather than fighting technology's pernicious effects, technology could be redesigned to produce alternative, more favorable effects.…”
Section: A Brief History Of Cyberdeliamentioning
confidence: 99%
“…Unsurprisingly, therefore, virtual reality technologies continue to hold a central place within the cyberdelic landscape. Some cyberdelic VR experiences promise to take users into a mystical Near Death Experience (Virtual Awakening, n.d.), others transport users into spectacularly colorful virtual worlds where sight and sound synesthetically mesh (Cyber Mushroom, 2022;Microdose, 2022), still other psychedelically inspired VR experiences like Isness purport to elicit empathy, ego dissolution and other Self-Transcendent Experiences (STEs) of the type induced by psychedelics by transporting users into a shared luminous virtual space where their beings are able to interact and even coalesce (Glowacki et al, 2020(Glowacki et al, , 2022. In some cases, developers put these technologies to empirical tests that claim to demonstrate commensurability between their effects and those of psychedelics (Schwartzman et al, 2019;Glowacki et al, 2020Glowacki et al, , 2022.…”
Section: The Current Cyberdelic Landscapementioning
confidence: 99%